Sigmoid ventricular septum treated with endocardial ablation to improve left ventricular outflow: cases report - Huang, Shen; Wang, Xiuyu; Li, Qiyan; Xiong, XinLin; He, Chuan; Feng, Kun; Jing, Jiafa; Ma, Jun (Frontiers in Cardiovascular Medicine, 2024)
Background Sigmoid Ventricular Septum (SVS) is a type of hypertrophic cardiomyopathy characterized by a reduced angle between the basal interventricular septum and the ascending aorta, and SVS can lead to dynamic Left Ventricular Outflow Tract obstruction (LVOTO) during hypercontractile states. Patients experiencing LVOTO may manifest symptoms such as angina, syncope, etc. Radiofrequency ablation (RFA) has been utilized to treat patients with hypertrophic obstructive cardiomyopathy, but there is no reports on its use in treating LVOTO resulting from SVS. Our report describes two cases of SVS treated with endocardial ablation to improve LVOTO. Case report Case 1: A 74-year-old female patient with angina and syncope was admitted to the hospital and diagnosed with SVS by transthoracic echocardiogram. The patient exhibited LVOTO and Systolic Anterior Motion (SAM) phenomena during the administration of the dobutamine stress test. After RFA was performed, the patient's symptoms significantly improved. Additionally, septum decreased from 16 to 13 mm after ten months, and the morphological changes associated with SVS also disappeared. Case 2: A 57-year-old female was admitted to the hospital due to recurrent chest pain after physical activity for more than four years. The transthoracic echocardiogram indicated that the patient met the diagnostic criteria for SVS, and LVOTO and SAM phenomenaoccurred following dobutamine stress test. The patient had significant improvement in symptoms after undergoing RFA treatment. Conclusions These two cases represent the first documented instances where dynamic LVOTO caused by SVS could be effectively managed through endocardial RFA.